Shading correction for whole slide image using low rank and sparse decomposition - Peng, Tingying; Wang, Lichao; Bayer, Christine; Conjeti, Sailesh; Baust, Maximilian; Navab, Nassir (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2014)
Many microscopic imaging modalities suffer from the problem of intensity inhomogeneity due to uneven illumination or camera nonlinearity, known as shading artifacts. A typical example of this is the unwanted seam when stitching images to obtain a whole slide image (WSI). Elimination of shading plays an essential role for subsequent image processing such as segmentation, registration, or tracking. In this paper, we propose two new retrospective shading correction algorithms for WSI targeted to two common forms of WSI: multiple image tiles before mosaicking and an already-stitched image. Both methods leverage on recent achievements in matrix rank minimization and sparse signal recovery. We show how the classic shading problem in microscopy can be reformulated as a decomposition problem of low-rank and sparse components, which seeks an optimal separation of the foreground objects of interest and the background illumination field. Additionally, a sparse constraint is introduced in the Fourier domain to ensure the smoothness of the recovered background. Extensive qualitative and quantitative validation on both synthetic and real microscopy images demonstrates superior performance of the proposed methods in shading removal in comparison with a well-established method in ImageJ. © 2014 Springer International Publishing.
CRIS-Team Scopus Importer:2023-03-08